Pemberdayaan Petani Jeruk di Desa Batukaang Kecamatan Kintamani Kabupaten Bangli - DHARMA, I GUSTI NGURAH KETUT SURYA; PARINING, NYOMAN; PUTRA, I GEDE SETIAWAN ADI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2021)
Empowerment of Citrus Farmers in Batukaang Village, Kintamani District, Bangli Regency Batukaang village is a citrus producing village located in Kintamani District. Almost all of the people in this village work as citrus farmers. During harvest season, citrus price fluctuates and all the farmers must sell their produce at low price. The study aims to assess the state of empowerment of citrus farmers based on “4 developments” theory. The study uses descriptive analysis method and involved 60 respondents determined through simple random sampling technique. The results of this study indicate that the condition of human development is in the fair category (35%), the condition of business development is in the poor category (41.7%), the condition of institutional development is in the excellent category (33.3%) and the condition of the environmental development is in the poor category (76,6%). It is recommended that extension agents should be more enthusiastic in guiding citrus farmers by presenting new innovations and information more frequently as well as spending more time in assisting the farmers. Citrus farmers should start processing their produce into a processed product to increase the price of the citrus and to avoid the price impact of the harvest. Farmers need to maintain their condition in institutional development and to use environmentally friendly inputs for the sustainability of agriculture in the area.